Acute Leg and Trunk Muscle Fatigue Differentially Affect Strength, Sprint, Agility, and Balance in Young Adults. Issue 8 (August 2021) - Roth, Ralf; Donath, Lars; Zahner, Lukas; Faude, Oliver
Abstract : Abstract: Roth, R, Donath, L, Zahner, L, and Faude, O. Acute leg and trunk muscle fatigue differentially affect strength, sprint, agility, and balance in young adults. J Strength Cond Res 35(8): 2158–2164, 2021—How important leg or trunk muscles are for balance and sprint performance is still unexplored. Therefore, we separately fatigued the leg and trunk musculature and examined their contribution to strength, balance, sprint, and agility performance. Twenty-four healthy adults (12 women; age 22.9 [ SD : 2.6] years; body mass 59 [10] kg; height 1.65 [0.09] m; and 12 men; age 22.7 [3.0] years; body mass 78 [9] kg; height 1.81 [0.06] m; at least 3 training sessions/week for at least 90 minutes) underwent a leg and a trunk fatigue procedure, each of 20-minute duration and a control condition at rest in a randomized order. Each condition was conducted individually on 3 separate days. Isokinetic leg and trunk strength, as well as static and dynamic balance, sprint, agility, and prone plank endurance, were assessed before and after each fatiguing protocol. Before assessment, a familiarization was conducted. Pairwise magnitude-based inference analyses showed likely relevant deterioration in leg (probability >87%; 0.36 < standardized mean differences [SMDs] < 0.92) and trunk (>88%, 0.28 < SMD < 0.74) fatigue procedures for all motor test parameters compared with the control condition, except for the 20-m sprint after the trunk fatigue procedure. Isokinetic strength testing revealed a large loss of strength in leg fatigue (particularly knee extension, 78%, SMD = 0.24) and trunk fatigue (trunk flexion, 100%, SMD = 1.36). Acute fatigue of leg and trunk muscles decreases performance in relevant measures of strength, balance, sprint, and agility. The impact of leg fatigue compared with trunk fatigue was larger in almost all measurements.